Electricity supply to agriculture in Andhra Pradesh and Punjab: Evolution and reform initiatives - Birner, Regina; Sharma, Neeru (International Food Policy Research Institute, 2011)
This chapter describes the political processes related to electricity subsidies, power-sector reforms, and irrigation- and groundwater-management policies.